2016
DOI: 10.1111/adj.12426
|View full text |Cite
|
Sign up to set email alerts
|

Platelet rich plasma and dentine effect on sheep dental pulp cells regeneration/revitalization ability (in vitro)

Abstract: A PRP scaffold has a positive effect on the proliferation, migration and differentiation of ODPC; however, dentine discs have an adverse effect on the activity of ODPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…A few studies pointed out that PRP could improve odontogenic/osteogenic differentiation [13,34,35] and mineralization [11,12] of dental stem cells. PRP promoted mRNA and protein expression of DSPP and DMP-1 in SCAP [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies pointed out that PRP could improve odontogenic/osteogenic differentiation [13,34,35] and mineralization [11,12] of dental stem cells. PRP promoted mRNA and protein expression of DSPP and DMP-1 in SCAP [13].…”
Section: Discussionmentioning
confidence: 99%
“…PRP is a favorable autologous scaffold that can facilitate cell proliferation and differentiation [10]. Dental pulp stem cells (DPSCs) cultured with a certain concentration of PRP exhibited preferable proliferation, migration, and mineralization [11,12]. SCAP cultured with PRP expressed a high level of odontogenic markers such as dentin matrix protein 1 (DMP-1) and dentin sialophosphoprotein (DSPP) [13].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 63 articles published between 1922 and 2002 alarmingly concluded that success rates of primary root canal treatment have not improved over the past 5 decades, ranging between 68% and 85% (Ng et al 2007). Therefore, current efforts are focused on different approaches to endodontic treatment, for example, revitalization of dental pulp to restore health inside the canal and promote the resolution of apical infection (Prescott et al 2008; Sun et al 2011; Huang and Garcia-Godoy 2014; Del Fabbro et al 2016; Altaii et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…29,30 While BC has been used traditionally as a scaffold in regenerative endodontic procedures, 31 alternatives such as scaffold with stem cells or growth factors have recently emerged as possible tools to enhance regeneration treatment outcomes. [32][33][34] It is worth noting that the use of alternative scaffolds or the addition of cells or materials to existing scaffolds may increase the required treatment sessions, the complexity of treatment, and the cost, plus it can potentially cause infection. Therefore, to justify these changes to the original scaffold, it is important to identify their effects on the tissues generated on the root walls and in the root canal space after treatment.…”
mentioning
confidence: 99%